2023
DOI: 10.1161/jaha.122.027414
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Computed Tomography for the Noninvasive Assessment of Arterial Aging: A Review by the VascAgeNet COST Action

Abstract: Magnetic resonance imaging and computed tomography allow the characterization of arterial state and function with high confidence and thus play a key role in the understanding of arterial aging and its translation into the clinic. Decades of research into the development of innovative imaging sequences and image analysis techniques have led to the identification of a large number of potential biomarkers, some bringing improvement in basic science, others in clinical practice. Nonetheless, the complexity of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Peripheral PWs differ from central PWs because of the effects of PW propagation and reflection along the arterial tree. Signals can be directly measured with methods such as pressure catheters, applanation tonometry, volume clamp method, oscillometric cuff ( 179 , 180 ), (Doppler) ultrasound ( 336 ), and magnetic resonance imaging (MRI) ( 181 ), but are also increasingly accessible to wearable technologies such as photoplethysmography ( 182 ), which is acquired by pulse oximeters and consumer devices (e.g., smartwatches and smartphones). These techniques are compared in Table 5 in terms of characteristics of the PW signals they measure and preferred features for measuring the PW in daily life.…”
Section: Pulse Wave Analysis Methodsmentioning
confidence: 99%
“…Peripheral PWs differ from central PWs because of the effects of PW propagation and reflection along the arterial tree. Signals can be directly measured with methods such as pressure catheters, applanation tonometry, volume clamp method, oscillometric cuff ( 179 , 180 ), (Doppler) ultrasound ( 336 ), and magnetic resonance imaging (MRI) ( 181 ), but are also increasingly accessible to wearable technologies such as photoplethysmography ( 182 ), which is acquired by pulse oximeters and consumer devices (e.g., smartwatches and smartphones). These techniques are compared in Table 5 in terms of characteristics of the PW signals they measure and preferred features for measuring the PW in daily life.…”
Section: Pulse Wave Analysis Methodsmentioning
confidence: 99%
“…This method does not directly measure the pulse wave in the aorta (like arterial tonometry), which may contribute to differences between the MRI investigations and the current study. Additionally, areas of aortic calcification can interfere with the accuracy of MRI measurements, and errors in blood pressure measurements can significantly affect the aortic distensibility calculation, particularly when brachial pressures are used to estimate aortic pulse pressure [83,84]. Although epidemiologic studies have shown that higher pulse pressure is associated with lower aortic root diameter [85][86][87], multiple studies show that smoking is associated with higher aortic diameter [86,[88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%